Power, Positionality, and Policymaking in Higher Education: Reflections on Student Lactation Support Initiatives - Whipps, Mackenzie; Dinour, Lauren; Vancour, Michele (Journal of Women and Gender in Higher Education, 2026)
In recent years, universities have extended lactation protections to students that have been traditionally afforded to paid employees only. Absent federal- and state-level regulation, this expansion has generally been piecemeal, taking place only when “breastfeeding advocates” request (or demand) those protections within their universities. Little research exists on these initiatives or about the breastfeeding advocates themselves. This article describes three examples of student lactation support initiatives on diverse U.S. university campuses. Using a comparative case study approach, the researchers examined the impact of positionality within higher education—and relative power afforded to different positions—on the initiatives and experiences of breastfeeding advocates. It is necessary to raise awareness and critically reflect on power structures to bring about change. The researchers found benefits of empowering students to engage in collective advocacy toward these ends, with practical implications for future U.S. lactation protection in academia. © 2026 NASPA—Student Affairs Administrators in Higher Education.
Keywords: dept.hhs

Community-engaged design of a virtual diabetes prevention program intervention with care coordination - LaMonaca, Katherine; Campbell-Britton, Meredith; Duffany, Kathleen O’Connor; Comerford, Beth P.; Morales, Sofia I.; Ayettey, Rockiy G.; Astudillo, Katia; Swansiger, Mary; Kidd, Claudette; Rue, Bailee; Santilli, Alycia; Njike, Valentine Y.; et al. (BMC Health Services Research, 2026)
The Diabetes Prevention Program (DPP) is an evidence-based approach to prevent Type 2 Diabetes (T2D), the leading cause of morbidity and mortality in the United States. Despite demonstrated benefits, acceptability and uptake of DPPs remain low, especially among communities with low incomes at increased risk for diabetes. The Yale-Griffin Prevention Research Center led the design of a community-engaged virtual DPP (vDPP) intervention and assessed its feasibility of implementation in two contrasting settings.
Keywords: Prediabetes; Prevention; Telemedicine; Type 2 Diabetes; dept.hhs

Re-Playing Majora’s Mask, College - Schriefer, Natalie (Medium, 2026)
The guard who calls you a child eventually recants.
Keywords: dept.hhs

’Backrooms’ Tests the Future of Horror Movies - Schriefer, Natalie (Bloomberg.com, 2026)
The film may determine how much Hollywood is willing to bet on other stories without a clear monster.
Keywords: A24; Backrooms; Bloomberg Graphics; Hollywood; Theater; culture; dept.hhs; gaming; graphic; indie games; internet; movies; opinion column

There's a Specific Type of Grief We Don't Talk About. Yoga Can Help You Process It. - Schriefer, Natalie (Yoga Journal, 2026)
Give yourself permission to feel everything.
Keywords: dept.hhs

Will CorePower Yoga Teachers Actually Go on Strike? - Schriefer, Natalie (Yoga Journal, 2026)
As February 1 draws closer, everyone is asking this question. Here's everything you need to know.

Building Power for Health: CARE’s Community Health Leaders Program - Santilli, Alycia; Morales, Sofia I.; Hodgson, Nora; Williams, Janice M.; Alvarez-Diaz, Isabel; Cole, Ayeisha; Abrams, Jasmine; Breny, Jean M.; O’Connor Duffany, Kathleen (Health Promotion Practice, 2026)
Individuals who face the daily impact of health inequities and their social drivers have knowledge and invaluable insights about solutions that are feasible at the local level. Community organizing is a dynamic and proven approach for building power among residents to identify community priorities, advocate for change, and co-create solutions to community issues, which has been applied to advance community priorities in the public health field. To build on evidence and further cultivate a pathway to strengthen community power and capacity within a public health framework, the Community Alliance for Research and Engagement (CARE), a health equity-focused partnership among Southern Connecticut State University, Yale School of Public Health, and the New Haven community, developed and implemented a new initiative, the Community Health Leaders (CHL) Program. The CHL program provides a model for community-centered leadership development as a strategy for advancing health equity. By equipping residents with the skills and support needed to advocate for change, CHL contributes to strengthening community power. Ultimately, continued investment in programs like CHL has the potential to create responsive public health programs and policies, reduce health inequities, and improve health outcomes. © 2026 Society for Public Health Education
Keywords: advocacy; community health; community organizing; dept.hhs; empowerment; health disparities; health equity; health promotion; lay leader advisors; social determinants of health; training

Introducing “Preservice Pipeline”—Why This Column, Why Now - Knipe, Bob (Journal of Physical Education, Recreation and Dance, 2026)
Future professionals learn to lead through a variety of professional opportunities, and it is time that JOPERD provides a forum dedicated to their development and an opportunity for them to lead as authors and coauthors. This article describes the new Preservice Pipeline column and how to submit articles. © 2026 SHAPE America.
Keywords: dept.hms

The Business Case for Breastfeeding: Identifying Which Barriers and Facilitators Employers Prioritize When Supporting Breastfeeding Employees in the Workplace - Frieson, Tomeka; Muhammad, Tila; Belyea, Monica; Cole, Ayeisha; Ray, Natasha; Duffany, Kathleen (Journal of Human Lactation, 2026)
Keywords: Breast feeding; Breastfeeding; Phone; Private sector; Public health; Space (punctuation); breastfeeding; breastfeeding barriers; breastfeeding benefits; breastfeeding experience; breastfeeding knowledge; breastfeeding promotion; breastfeeding support; dept.hhs; maternal health; public health; qualitative methods; social support

Komi Can't Communicate: Making Friends and Not Scaring People - Oda, Tomohito; Schriefer, Natalie (2026)
Learn to make friends and stop scaring people away with this clever book inspired by the hit manga Komi Can’t Communicate.Do you find it hard to sp...

Empowering the self: Flow state in The Legend of Zelda: Breath of the Wild and Tears of the Kingdom - Schriefer, Natalie (Journal of Gaming & Virtual Worlds, 2026)
Keywords: Creativity; Flow (mathematics); Identification (biology); Legend; State (computer science); Tears; dept.hhs